Children's perspectives on domestic violence - Mullender, Audrey (SAGE, 2002)
Children's Perspectives on Domestic Violence examines children's experiences and perspectives on living with domestic violence. Offered is a detailed explanation of the impact on children living with domestic violence, how children make sense of and cope with their experiences, the response they receive from various agencies and the fit between what children feel they need and what in reality they receive.